Five-year real-world outcomes of short-course leukocyte-poor PRP versus standard conservative therapy in early-stage knee osteoarthritis - Qiuping Yu; Chenghong Wen; Junli Liu (PLoS ONE, 2026)
Background Platelet-rich plasma (PRP) is increasingly applied in knee osteoarthritis (KOA), but its long-term efficacy remains uncertain. This study assessed 5-year outcomes of intra-articular PRP compared with conventional therapy in early-stage KOA. Methods A retrospective cohort of 116 patients with bilateral KOA (Kellgren–Lawrence I–II) treated in 2019 was analyzed. Group A (n = 58) received standardized management plus three PRP injections, while Group B (n = 58) received standardized conservative management alone (NSAIDs and/or intra-articular hyaluronic acid), combined with education, exercise therapy, and weight management. Pain, function, and quality of life were evaluated by VAS, WOMAC, and SF-36 at baseline and 5 years. Results Both groups showed deterioration over 5 years. VAS increased from 4.64 ± 0.52 to 5.41 ± 1.17 in Group A and from 4.80 ± 0.59 to 5.44 ± 1.16 in Group B, without significant between-group difference ( P = 0.849). WOMAC and SF-36 scores also worsened similarly, with no intergroup significance ( P > 0.05). Intra-group analyses confirmed significant declines from baseline ( P < 0.001). Conclusions Although a short, single course of leukocyte-poor PRP did not yield sustained superiority over standardized conservative management at 5 years, this real-world study provides rare long-term comparative evidence that defines the temporal boundaries of PRP efficacy and underscores the need for maintenance or optimized dosing protocols in clinical practice.